The effect of supplementsl irrigation, foliar fertilization and NAA hormone on the alternate bearing in pistachio (pistacia vera L.) - Alahmad, Abdullah Mohammad; Kerdush, Muhammed Absi; Dairy, Muhammed Ayman (Journal of agricultural, environmental and veterinary sciences, 2021)
This research (study)was carried out over four years (2017-2020) on Ashori pistachio nut cultivar in a pistachio orchard located in Soran/Hama region (SYRIA) in order to determine the effect of leaves fertilisation, supplementsl irrigation, and NNA treatment on bud shedding, yield, and nut splitting rate in pistachio trees.The experiment was designed according to the split-split-pot designs, where the main plots included supplementsl irrigation treatment (without irrigation, winter irrigation, summer irrigation, winter and summer irrigation) and the first-order plots included leaves fertilization concentrations (0, 1 and 2 g.liter -1) and the second-order plots included NAA levels (0, 25 and 50 ppm). The results indicated that the percentage of floral buds falling down during the fruit yield season, was higher than the non-fruit yield season and it was at its lowest in the third season because of the combined effect of fertilization (2g/lit) and NAA (50 ppm) and it reached (30.9%) and followed by the treatment of NAA (50 ppm) which reached (31.2%). The yield average was at its highest in the fourth fruit yield season (39.49 kg) at the fourth irrigation treatment (winter + summer) whit it was in the control treatment) 29.17 kg). The average percentage of nut splitting in the fourth season was (97.1%) for the effect of fourth irrigation treatment and fertilization level (1 g/lit), followed by the fourth irrigation treatment which the nut splitting was (96.77%).
Keywords: Pistacia vera; supplementsl irrigation; Foliar fertilization; NAA; Productivity